PENGEMBANGAN INOVASI BARU TERHADAP OLAHAN BUAH NANAS (INOVASI KERUPUK GANDUM NANAS) - Endah Panca Wijayanti1, Tirsa Neyatri Bandrang2 (Politeknik Seruyan, 2024)
The development of new innovations in processed pineapple fruits through Pineapple Wheat Cracker products is part of an entrepreneurship program aimed at students. This product combines pineapple base with wheat, resulting in a snack that not only has a unique taste, but also high nutritional benefits. Pineapple Wheat Crackers are available in various packaging sizes ranging from 100 gr to 250 gr, with selling prices ranging from Rp. 7,000 to Rp. 20,000. This product is offered in two variants, namely ready-to-eat crackers and raw crackers that can be further processed by consumers. Sales are carried out through retail or unit methods, and can be marketed online or through distribution at nearby restaurants and stores. This innovation aims to provide healthy snack alternatives that can be accepted by the wider community, as well as provide business opportunities for students in developing entrepreneurial skills and marketing locally-based food products. Keywords: Entrepreneurship, Pineapple Wheat